2018
DOI: 10.5194/acp-18-129-2018
|View full text |Cite
|
Sign up to set email alerts
|

Mercury fluxes over an Australian alpine grassland and observation of nocturnal atmospheric mercury depletion events

Abstract: Abstract. Aerodynamic gradient measurements of the airsurface exchange of gaseous elemental mercury (GEM) were undertaken over a 40 ha alpine grassland in Australia's Snowy Mountains region across a 3-week period during the late austral summer. Bi-directional GEM fluxes were observed throughout the study, with overall mean value of 0.2 ± 14.5 ng m −2 h −1 and mean nocturnal fluxes of −1.5 ± 7.8 ng m −2 h −1 compared to diurnal fluxes of 1.8 ± 18.6 ng m −2 h −1 . Deposition velocities ranged from −2.2 to 2.9 cm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 72 publications
4
36
2
Order By: Relevance
“…Micrometeorological Hg flux measurements undertaken in sub-alpine south-eastern Australia (Nimmo Plain) during summer had an average Hg flux of 0.2 ng m -2 h -1 (SD ± 14.5 ng m -2 h -1 ) (Howard and Edwards, 2018), comparable to the summer fluxes observed at Oakdale (0.67 ng m -2 h -1 , SD ± 7.76 ng m -2 h -1 ). Flux chamber measurements at a background site (Pulganbar, north-eastern New South Wales) observed average fluxes of 0.17 ng m -2 h -1 (SD ± 0.09 ng m -2 h -1 ) in both April and June (Edwards and Howard, 2013), whereas Oakdale experienced net deposition during this time.…”
Section: Mercury Fluxesmentioning
confidence: 53%
See 1 more Smart Citation
“…Micrometeorological Hg flux measurements undertaken in sub-alpine south-eastern Australia (Nimmo Plain) during summer had an average Hg flux of 0.2 ng m -2 h -1 (SD ± 14.5 ng m -2 h -1 ) (Howard and Edwards, 2018), comparable to the summer fluxes observed at Oakdale (0.67 ng m -2 h -1 , SD ± 7.76 ng m -2 h -1 ). Flux chamber measurements at a background site (Pulganbar, north-eastern New South Wales) observed average fluxes of 0.17 ng m -2 h -1 (SD ± 0.09 ng m -2 h -1 ) in both April and June (Edwards and Howard, 2013), whereas Oakdale experienced net deposition during this time.…”
Section: Mercury Fluxesmentioning
confidence: 53%
“…Relative humidity has been suggested as an indicator of Hg deposition occurring via condensation of water onto the surface vegetation, whereby higher humidity indicates more potential for condensation to occur (Fritsche et al, 2008). Howard and Edwards (2018) suggested that nocturnal Hg depletion events were caused by dew formation and fog creating potential sinks of Hg. Spring diel trends exhibit deposition leading up to sunrise which then shift to emission shortly after sunrise (Figure 3).…”
Section: Mercury Flux Variation Across Seasonsmentioning
confidence: 99%
“…1). Nam Co Station was established in 2005 to maintain a long-term record of the meteorological, ecological and atmospheric measurements on the Tibetan Plateau (Cong et al, 2007;Li et al, 2007;Kang et al, 2011;Huang et al, 2012;Liu et al, 2015;de Foy et al, 2016b). There are restricted point sources of anthropogenic mercury emissions near Nam Co Station.…”
Section: Measurement Sitementioning
confidence: 99%
“…Further, it has been increasingly perceived that the inland Tibetan Plateau can be influenced by transboundary air pollution such as black carbon originating from biomass burning in South Asia, which crosses the Himalayas (Xia et al, 2011;Cong et al, 2015;Wan et al, 2015;Li et al, 2016). Studies of mercury in precipitation and water vapor evidenced that the Tibetan Plateau is likely sensitive to pollutant input including mercury (Huang et al, 2012(Huang et al, , 2013. Furthermore, the particulate-bound mercury in total suspended particulates was found at high concentrations in Lhasa with an average of 224 pg m −3 , which was comparable to other cities in China (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Photo-reduction is a major driver of TGM evasion from the Earth's surface (Howard and Edwards, 2018;Kuss et al, 2018;Gao et al, 2020), and this is due to photochemically mediated reduction that converts soil Hg 2+ to volatile Hg 0 and enhances the Hg 0 pool in the soil pore (Xin and Gustin, 2007;Choi and Holsen, 2009a). Therefore, the elevated soil pore Hg 0 concentrations increased the potential of soil pore TGM diffusion to the atmosphere, which drives an increase of Hg emissions from soil.…”
Section: Correlations Between Environmental Factors and Fluxesmentioning
confidence: 99%